EVALUATING THE ONLINE SERVICE QUALITY SYSTEM ON LION AIRLINE TICKETS SALES IN MANADO USING IMPORTANCE AND PERFORMANCE - Mambu, Angelia Christa; Pandowo, Merinda . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract :Airline Reservation System (ARS) used to be standalone systems. Each airline had its on system, disconnected from other airlines. Air travel information is linked, stored and retrieved by network of Computer Reservation System (CRS) accessible by multiple.This research aims to analyze the service quality of online reservation system in Manado. In this case Lion works with rhe help of the different diagrams and illustrations. The thesis concluded that with the progress of ever-changing technology, the trend of booking online is likely to develop with more feature. While there are a few limitations, the convinence of booking tickets online and the possible enchancements will lead to an even advanced from of booking tickets online.The result showsFurthermore, based on the result, online reservation system on Lion Airline ticket sales shouldmaintain their good service and should improve their low performance. By doing so, it is hoped that the customer Lion Airline will besatisfied and will be their loyal customer.Keywords: service quality, importance perfromace analysis, online Â reservation system, lion airline ticket sales